PENGAMATAN PENDAHULUAN OVARIUM BANDIKUT (Echymipera kalubu): PRELIMINARY OBSERVATION ON OVARIAN OF BANDICOOT (Echymipera kalubu) - Fahry Rafli; Angel N. Tethool; Freddy Pattiselanno (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2018)
The study aimed to determine the size and physical description (location, shape, colour and texture) ovarian of Echymipera kalubu. Study was conducted in 3 months from June to September 2017. Three female E. kalubu with an average body weight 399±97.32g and average body length 21.67±5.51cm were used in this study. Sample of bandicoots were dissected using a surgical tool and then measured using measuring tester and analytic scales. Descriptive statistics was used to analyse the data. The results showed that average length of female reproductive organs of E. kalubu was 11,00±0,87 cm (right) and 11,03±0,83 cm (left); average weight of ovarian was 0,01±0,0048 g (right) and 0,02±0,0006 g (left). This study also showed that characteristics of ovarian were in common with other polytocus animals.